2000
DOI: 10.1128/jvi.74.19.8812-8822.2000
|View full text |Cite
|
Sign up to set email alerts
|

The 60-Residue C-Terminal Region of the Single-Stranded DNA Binding Protein of Herpes Simplex Virus Type 1 Is Required for Cooperative DNA Binding

Abstract: Single-stranded (ssDNA) DNA binding proteins (SSBs) bind preferentially ssDNA in stoichiometric quantities with respect to their substrate, displaying little sequence preference and no associated ATPase activity (11). The binding is typically cooperative, though the level of cooperativity varies widely. Much effort has been spent on elucidation of the structural mechanism accounting for the cooperativity and its functional implications in the case of the filamentous phage GVP (6, 68), the phage T4 gp32 (10, 33… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
28
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 80 publications
2
28
1
Order By: Relevance
“…3) (65). Truncated ICP8 still binds ssDNA but with loss of cooperativity (66). The crystal structure reveals a large N-terminal domain (residues 9 -1038) and a small C-terminal domain (residues 1049 -1129).…”
Section: Properties Of Replisome Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…3) (65). Truncated ICP8 still binds ssDNA but with loss of cooperativity (66). The crystal structure reveals a large N-terminal domain (residues 9 -1038) and a small C-terminal domain (residues 1049 -1129).…”
Section: Properties Of Replisome Proteinsmentioning
confidence: 99%
“…The process has been visualized demonstrating how two coiled ICP8-ssDNA nucleoprotein filaments generate intertwined coiled-coil structures in which strand annealing occurs (66). ICP8 has also been demonstrated to promote strand invasion in vitro, and together with helicaseprimase, it can promote strand exchange (67,68).…”
Section: Properties Of Replisome Proteinsmentioning
confidence: 99%
“…HSV ICP8 is characterized by highly cooperative and DNA sequence-independent ssDNA-binding (21) with an apparent binding constant (K ␣ ) for monomeric ICP8 on ssDNA in the range of 1 ϫ 10 7 M Ϫ1 (1,7,20). Electron microscopy confirmed the highly cooperative but unspecific nature of ICP8 binding to ssDNA (18,25) whereas Rep molecules on the AAV ssDNA genome bind exclusively to the hairpin-shaped ITR that contains the RBS (14,15,34,37).…”
mentioning
confidence: 85%
“…Furthermore, direct AAV ssDNA-dependent interaction of purified ICP8 and Rep78 was shown in vitro (10). ICP8 displays high-affinity, cooperative binding to ssDNA (1,7,20). Rep78/68 also displays some ssDNAbinding activity (16,19,36) but preferentially binds to the doublestranded RBS within the hairpin-shaped AAV ITR (12).…”
mentioning
confidence: 99%
“…ICP8 is a 128-kDa protein able to form protein filaments in the absence of DNA, although it sediments as a monomer in glycerol gradients (36). Deletion of its 60-amino acid C-terminal region does not affect the intrinsic DNAbinding ability of the protein, but results in a total loss of cooperativity on long ssDNA stretches (37). It has been demonstrated that ICP8 interacts with other components of the replication machinery, like UL9 protein helicase (38 -40) or the herpes simplex virus-1 DNA polymerase and helicase-primase (41)(42)(43)(44)(45).…”
Section: Visualization Of the Deletion Mutant Proteins By Electronmentioning
confidence: 99%